A novel fuzzy edge detection of seismic images based on bi-level maximum entropy thresholding. (16th November 2010) - Singh, Sanjay Kumar; Pal, Kirat; Nigam, M.J.
The study of edge detection techniques in earthquake engineering is extremely important for recognition of seismic faults in the viewpoint of disaster prevention. Further, Seismic datasets are huge (several terabytes), redundant and complex. Hence, cost increases to large extent for storage and transmission against the limited memory and bandwidth. This paper presents a novel fuzzy edge detection technique of seismic images based on bi-level maximum entropy thresholding principle. Seismic edge images are obtained based on the concept of fuzzy conditional probabilities, fuzzy partition and adaptively searching the two-level optimal threshold through maximum fuzzy entropy of seismic gradient images.